A History of the Academy of Human Resource Development: An Introduction. (November 2016) - Watkins, Karen E.
The Problem: As the founders of the Academy of Human Resource Development [AHRD] begin to retire, the story of the evolution of this academic field has not been captured. The Solution: This issue looks at the early beginnings of an academic emphasis in human resource development (HRD) and the professional association they formed to support and enhance academic programs from the voices of those who have played key roles in the founding of the Academy. The Stakeholders: What is important to practitioners to know is that this association is part of a larger process of professionalization and certification of practitioners in the field. These efforts have the potential to ensure that all who practice in HRD are recognized as professionals with a unique body of knowledge. For scholars, theory development in HRD has been a significant thrust of several of the scholars included in this issue, and some of the articles proposed have the potential to identify areas where we need to encourage new theory development. Practitioners will find a thread that connects the mission of the AHRD to advance the profession through research with the way HRD professionals are educated at the institutions offering these degrees. At the same time, in the reciprocal and reflexive nature of this field, practice also helps shape the research agenda.